Arginine effects on biochemical composition of sperm in rainbow trout, Oncorhynchus mykiss. (4th August 2016) - Pourkhazaei, Fateme; Ebrahimi, Eisa; Ghaedi, Alireza
Summary: The present study investigated the effect of arginine on seminal plasma composition in rainbow trout. Male rainbow trout broodstocks (2500 ± 200 g) were fed five practical diets (each consisting of three triplicates) supplemented with Arginine at 0.50%, 1.50% and 2.00%. The control group were fed without arginine. Broodstock feeding lasted for 90 days, and then fish semen was sampled. Results indicated no significant differences in LDH, ALP, Fe 2+ and phosphorous content among the different treatments. The lowest levels of AST and ALT and the highest levels of Ca 2+ and Mg 2+ ions were observed in the treatment fed with 1.50% arginine, which showed significant differences from other treatments ( P < 0.05). Moreover, the amount of Cl −, Na + and K + ions was significantly increased in the seminal plasma in fish fed diets containing arginine in comparison with the control. As the amount of arginine was increased, the levels of uric acid became significantly greater in contrast to urea and glucose levels. The highest amounts of cholesterol, fructose and total protein were observed in treatments fed on 2.00%, 0.50% and 1.00% arginine, respectively, showing significant differences from other treatments ( P < 0.05). The highest pH value was assayed in the 1.50% arginine treatment. Results indicated that arginine had a potential efficacy on semen quality in rainbow trout broodstocks.